Common genetic polymorphism at 4q25 locus predicts atrial fibrillation recurrence after successful cardioversion - Parvez, Babar; Shoemaker, M. Benjamin; Muhammad, Raafia; Richardson, Rachael; Jiang, Lan; Blair, Marcia A.; Roden, Dan M.; Darbar, Dawood (Heart rhythm, 2013)
Genome-wide association studies have identified numerous common polymorphisms associated with atrial fibrillation (AF). The 3 loci most strongly associated with AF occur at chromosome 4q25 (near PITX2), 16q22 (in ZFHX3), and 1q21 (in KCNN3). To evaluate whether timing of AF recurrence after direct current cardioversion (DCCV) is modulated by common AF susceptibility alleles. A total of 208 patients (age 65±11 years; 77% men) with persistent AF underwent successful DCCV and were prospectively evaluated at 3, 6, and 12 months for AF recurrence. Four single nucleotide polymorphisms—rs2200733 and rs10033464 at 4q25, rs7193343 in ZFHX3, and rs13376333 in KCNN3—were genotyped. The final study cohort consisted of 184 patients. In 162 (88%) patients, sinus rhythm was restored with DCCV, of which 108 (67%) had AF recurrence at a median of 60 (interquartile range 29–176) days. In multivariable analysis, the presence of any common single nucleotide polymorphism (rs2200733, rs10033464) at the 4q25 locus was an independent predictor of AF recurrence (hazard ratio 2.1; 95% confidence interval 1.21–3.30; P = .008). Furthermore, rs2200733 exhibited a graded allelic dose response for early AF recurrence (homozygous variants: 7 [interquartile range 4–56] days; heterozygous variants: 54 [28–135] days; and wild type: 64 [29–180] days; P = .03). To our knowledge, this is the first study to evaluate whether genomic markers can predict timing of AF recurrence in patients undergoing elective DCCV. Our findings show that a common polymorphism on chromosome 4q25 (rs2200733) is an independent predictor of AF recurrence after DCCV and point to a potential role of stratification by genotype.